Analysis of the influence of students interest in entrepreneurship - Riza, dessy selvia; Wulandari, Wulandari; Rosia, Rina (Islamic Accounting Journal, 2024)
This study aims to determine student interest and the factors that influence student interest in the Faculty of Economics and Islamic Business (FEBI) of the Salatiga State Islamic Institute (IAIN Salatiga) in entrepreneurship. The method used is quantitative methods, with research techniques namely multiple linear regression analysis, classical assumption test, hypothesis testing and coefficient of determination with the help of SPSS version 25 software. The sampling determination technique is probability sampling and purposive sampling with the help of a questionnaire in collecting distributed data to 30 students as respondents. The results showed that entrepreneurship education, accounting information and social media had an effect on student interest in entrepreneurship and environment and religiosity had a negative effect on student interest in entrepreneurship. Simultaneously entrepreneurship education, accounting information, environment, social media, and religiosity affect student interest in entrepreneurship.